2020
DOI: 10.1002/ece3.6235
|View full text |Cite
|
Sign up to set email alerts
|

Silicon‐mediated multiple interactions: Simultaneous induction of rice defense and inhibition of larval performance and insecticide tolerance of Chilo suppressalis by sodium silicate

Abstract: The rice striped stem borer (SSB, Chilo suppressalis) is one of the most destructive pests of rice plants. Si‐mediated rice defense against various pests has been widely reported, and sodium silicate (SS) has been used as an effective source of silicon for application to plants. However, there is quite limited information about the direct effects of Si application on herbivorous insects. SSB larval performance and their insecticide tolerance were examined after they had been reared either on rice plants cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Despite having lower Si concentrations there were no differences in herbivore feeding, relative growth Frew et al 2019, Hall et al 2020a, and that increases in foliar Si accumulation in response to herbivore signals occur rapidly (Waterman et al 2021b), but this is the first demonstration of how quickly plants previously unexposed to Si incorporate it into their tissues as an effective antiherbivore defense. A recent study by Wang et al (2020) found that Chilo suppressalis (Lepidoptera) growth was equally suppressed when feeding on plants supplemented with either 0.5 mmol/L or 2 mmol/L calcium silicate solution compared to nonsupplemented plants, despite the fact that plants grown in 2 mmol/L solution had over 1.5 times higher stem Si concentrations. Plants might only require a certain amount of Si accumulation to reach the same level of resistance as would be achieved with much higher concentrations, and here we report that this threshold may be reached much faster than previously envisaged.…”
Section: Short-term Exposure To Si Reduces Herbivore Performancementioning
confidence: 99%
“…Despite having lower Si concentrations there were no differences in herbivore feeding, relative growth Frew et al 2019, Hall et al 2020a, and that increases in foliar Si accumulation in response to herbivore signals occur rapidly (Waterman et al 2021b), but this is the first demonstration of how quickly plants previously unexposed to Si incorporate it into their tissues as an effective antiherbivore defense. A recent study by Wang et al (2020) found that Chilo suppressalis (Lepidoptera) growth was equally suppressed when feeding on plants supplemented with either 0.5 mmol/L or 2 mmol/L calcium silicate solution compared to nonsupplemented plants, despite the fact that plants grown in 2 mmol/L solution had over 1.5 times higher stem Si concentrations. Plants might only require a certain amount of Si accumulation to reach the same level of resistance as would be achieved with much higher concentrations, and here we report that this threshold may be reached much faster than previously envisaged.…”
Section: Short-term Exposure To Si Reduces Herbivore Performancementioning
confidence: 99%
“…Si also modifies the production of plant volatiles and enhances recruitment of herbivores' natural enemies (Kvedaras et al, 2010 ; Liu et al, 2017 ; Leroy et al, 2019 ). Insects exposed to Si-treated plants have exhibited reduced growth and development (Frew et al, 2017 ; Yang et al, 2018 ), alterations of feeding behavior (Assis et al, 2013 ), changes in oviposition preference (Peixoto et al, 2011 ), increased mortality (Han et al, 2015 ), lower fecundity (Alvarenga et al, 2017 ), and increased susceptibility to insecticides (Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, research has waved to put efforts to understand the effect of Si on mitigation of abiotic and biotic stresses [ 9 , 10 , 11 ], with drought and salinity as the two most frequent stress triggers. The role of Si has also been identified as an inducer of plant defense and as an inhibitor of insect resistance to insecticide and thus a good candidate for pest management in the field [ 12 ]. Among abiotic stresses, a conclusive role of Si in alleviation of individual MN deficiencies has also been demonstrated [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%